Urgent Video Electroencephalography (EEG) in the Pediatric Emergency Department: Is It Useful? - Mohammad Y. Sawahreh (21480203) (2025)
Introduction Seizures account for about 1% of Pediatric Emergency Department (PED) visits. Electroencephalography (EEG) is essential for evaluating seizures and other neurological concerns. The utility of urgent video EEG (vEEG) in the PED remains unclear. Objective To study the role of urgent vEEG in evaluating children presenting with seizures and other paroxysmal events through a retrospective chart review analysis conducted at a single tertiary children’s hospital over a 3-year period. Results 277 patients underwent vEEG (142 females (52%); mean age 7.7 years). Most common indications were new onset paroxysmal events (37%) and first unprovoked seizure (20%). vEEG was performed within 24 hours of the event and sleep was achieved in 92% and 80% of patients respectively. Most patients (61%) had abnormal findings. Perinatal risk factors, pre-existing developmental delay, pre-established epilepsy and an abnormal neurological examination highly correlated with vEEG abnormalities (p< 0.05). Clinical events captured during monitoring differentiated epileptic from non-epileptic episodes (16%). New onset paroxysmal events were diagnosed as epileptic in 60%. Specific epilepsy syndromes were identified in 57% of this subgroup. vEEG contributed to initiation of anti-seizure medications (47%) and impacted decisions to change anti-seizure medications in 67% of known patients with epilepsy. Abnormalities on neuroimaging were found in approximately half of patients with abnormal vEEG who were imaged. Conclusion This study suggests that urgent vEEG in PEDs can lead to early diagnosis and treatment, reduce the need for further investigations, and potentially improve outcomes. However, the cost-effectiveness and availability of vEEG in PEDs need further evaluation. Other Information Published in: Pediatric Neurology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.pediatrneurol.2025.05.024